Affective and effective truths: Rhetoric, normative and critical management studies - Parker, Simon and Racz, Marton (Organization)
In an era of Brexit, Trump and the detritus of post-truth politics, this article calls upon critical management scholars to reflect upon the efficacy of their critique. We examine the post-truth critiques of public relation firms working for tobacco corporations in the 1960s, before discussing contemporary examples of the Flat Earth Society and the growing community of climate change deniers. In doing so, we note similarities to the intellectual tactics and strategies of the critical management community in terms of problematizing truth(s), broader aims to counter mainstream discourses of science and the various attempts to provide alternative perspectives on the world. In learning from these post-truth communities, we argue that the critical community should be wary of falling back onto a rational, logical and potentially elitist platform of Socratic critique and conversely should not refuse dialogue as in cynical critique. Instead, we argue for more agonistic forms of critique that use salient exemplars to develop affective relationships within communities alongside the discussion of facts, ethics and politics.- Reproduced
Keywords: Agonism, Critical management studies, Post-truth, Rhetoric